2019
DOI: 10.1186/s12917-018-1772-x
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 expression and prognostic significance in feline invasive mammary carcinomas: a retrospective observational study

Abstract: BackgroundCats spontaneously develop invasive mammary carcinomas with high clinical aggressiveness, and are considered relevant animal models for human breast cancer. Bcl-2 is an anti-apoptotic pro-survival protein, whose expression is associated with a favorable outcome in human breast cancer. The aim of our study was to determine the frequency of Bcl-2 expression in feline invasive mammary carcinomas (FMCs), its relationship with other clinicopathologic variables, and its prognostic value. This retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 67 publications
(104 reference statements)
1
22
0
Order By: Relevance
“…Histological examination was performed on 3-μm-thick hematoxylin–eosin-saffron (HES) stained whole sections (not partial biopsies) of feline mammary carcinomas. Histological types, histological grades according to Elston & Ellis' criteria (61), lymphovascular invasion (LVI), local invasion of dermis or muscle, tumor-associated inflammation, central necrosis, ulceration, squamous differentiation, margin status, and pathologic nodal stage (pN) were evaluated as previously described (35, 62). The pathologic tumor size (pT) was measured as described for dogs in Part 1 of this article.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Histological examination was performed on 3-μm-thick hematoxylin–eosin-saffron (HES) stained whole sections (not partial biopsies) of feline mammary carcinomas. Histological types, histological grades according to Elston & Ellis' criteria (61), lymphovascular invasion (LVI), local invasion of dermis or muscle, tumor-associated inflammation, central necrosis, ulceration, squamous differentiation, margin status, and pathologic nodal stage (pN) were evaluated as previously described (35, 62). The pathologic tumor size (pT) was measured as described for dogs in Part 1 of this article.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry (IHC) was performed using a Benchmark XT automated instrument (Ventana Medical Systems, Roche Diagnostics) as described in Part 1 and a previous study (62), using antibodies to p63 (monoclonal mouse anti-p63 antibody, clone 4A4, abcam ab735, 1:100), pancytokeratin (mouse monoclonal, clones AE1/AE3, Dako, 1:200), Estrogen Receptor alpha (ER, mouse monoclonal, clone C311, Santa Cruz Biotechnology, dilution 1:50), Progesterone Receptor (PR, mouse monoclonal, clone 10A9, Meridian Life Science, 1:50), Human Epidermal growth factor Receptor Type 2 (HER2, rabbit monoclonal, clone 4B5, Roche Diagnostics, prediluted), and Ki-67 (mouse monoclonal, clone MIB1, Dako, dilution 1:50). For invasive mammary carcinomas, IHC to cytokeratins 5 and 6 (CK5/6, mouse monoclonal, clone D5/16B4, Dako, dilution 1:50), cytokeratin 14 (mouse monoclonal, clone LL002, Santa Cruz Biotechnology, dilution 1:100), Epidermal Growth Factor Receptor Type 1 (EGFR, rabbit monoclonal, clone 5B7, Roche Diagnostics, prediluted), and LMO2, which in cats is a lymphatic endothelial marker and helped in LVI assessment (LIM domain-only protein-2, clone SP51, Spring M351, 1:150) were also performed (35).…”
Section: Methodsmentioning
confidence: 99%
“…This retrospective study included 180 cats with invasive mammary carcinomas, which have been previously described. 36 Female cats were eligible for inclusion if they had an invasive mammary carcinoma, if they were treated solely by surgery, and if follow-up was available for at least 2 years post-mastectomy.…”
Section: Animals and Inclusion Criteriamentioning
confidence: 99%
“…Recorded histological data were the histological types, lymphovascular invasion (LVI), histological grade according to the Elston and Ellis grading system for human breast cancer, 39 which has been validated in FMCs, 40 presence/absence of central necrosis or squamous differentiation, and tumorassociated lymphohistiocytic inflammation, as previously described. 36 The pathologic tumor (pT) size was measured on histological sections as the greatest tumor diameter, in millimeters. This was achieved on a single slide for tumors of \25 mm (inner dimension of a histological cassette), or on two adjacent slides for tumors of 25-50 mm in diameter.…”
Section: Histopathologymentioning
confidence: 99%
“…Recently the receptor CXCR4 and its ligand CXCL12 have been studied in FMT, and decreased CXCL12 was associated with poor prognosis, but only in tumors highly expressing HER2 [48]. Staining primary tumors for Bcl-2, an anti-apoptotic protein, revealed that increased Bcl-2 positivity was associated with longer survival, disease-free survival and cancer-specific survival [49]; however only a small proportion of FMT were positive for Bcl-2 in this study, and thus this marker may only be used to prognosticate a subpopulation of feline patients. Consistent with the ability of SDF-1 to predict outcome in human patients, SDF-1 was also found to be higher in cats with FMT compared to healthy individuals, although it was unable to predict outcome [50].…”
Section: Plos Onementioning
confidence: 99%